2020
DOI: 10.1111/pai.13315
|View full text |Cite
|
Sign up to set email alerts
|

Maternal microbiome regulation prevents early allergic airway diseases in mouse offspring

Abstract: Background: Asthma is a serious global health problem, severely affecting the lives of sufferers and their families. An exceptionally hygienic home and reduced microbial exposure can aggravate the incidence of childhood asthma. Methods: Specific-pathogen-free BALB/c mice were pre-treated with bacterial lysate (BL; 1 mg/kg) as a high microbial load maternal mouse model, and then, the offspring mice were established as an allergic airway disease (AAD) model. The expression levels of TLR2, TLR4, and HDAC9 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…That means TLR2 may induce remission of asthma [35]. Another study in mouse also suggested appropriate stimulation of the TLR2/4 pathway may help to prevent asthma later in life [36]. Thus, further studies are needed to reveal the effect of TLR2 on asthma and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…That means TLR2 may induce remission of asthma [35]. Another study in mouse also suggested appropriate stimulation of the TLR2/4 pathway may help to prevent asthma later in life [36]. Thus, further studies are needed to reveal the effect of TLR2 on asthma and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Since the primary source of microorganisms that will colonize and shape the microbiota of the newborn comes from the maternal origin, it is worth asking whether there is a connection between dysbiosis of the maternal microbiota and the development of diseases in adulthood, such as metabolic and cardiovascular diseases, neurodevelopment alterations or changes in the immune system. Supplementary Table 1 shows different studies describing this relationship (10).…”
Section: Diseases Of Adulthood and Their Relationship To Maternal Mic...mentioning
confidence: 99%
“…In contrast, the control progeny showed elevated IL-4 and IL-5 concentrations and GATA3 expression. An essential element recognized in the mothers of the intervention group was the decrease in histone deacetylase 9 expression, suggesting possible epigenetic mechanisms by which the microbiota reduces the risk of developing allergic diseases (10).…”
Section: Allergy and Atopic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have found that in-utero exposures to environmental factors, such as cigarette smoking during pregnancy [70][71][72], maternal diet [73][74][75][76], and microbial exposures [77,78], also have a dramatic influence on the risk of allergic disease in the offspring by altering fetal lung development and immune function [79]. Results from "The Managing Asthma in Pregnancy (MAP) Study" provided the first demonstration that exposure to maternal asthma during pregnancy is associated with alterations in the DNA methylation profile of infants' peripheral blood.…”
Section: Fetal Epigenetic Changes: Studies On Cord Blood Cellsmentioning
confidence: 99%